Asset misappropriation in small businesses. Issue 2 (8th May 2018) - Kennedy, Jay P.
Abstract : Purpose: This paper aims to increase the understanding of the types of insider financial frauds that occur within small businesses by focusing on a sample of businesses that have not employed a certified fraud examiner (CFE) in response to employee theft. Design/methodology/approach: The survey data analyzed come from 102 small businesses (100 employees or fewer) in a midsized Midwestern city in the USA, and reflect 125 reported employee thefts. Findings: The study results indicate that small businesses that do not hire a CFE report certain thefts with greater and lower frequencies as compared to small businesses that do hire a CFE. For particular types of frauds, CFEs may be no more useful than the efforts of business owners or managers, and other employees. Practical implications: There may be important organizational differences between businesses that hire CFEs and those that do not, differences related to the ways in which business finances are maintained, the ways in which specific controls are used and the ability of employees to access business resources. These factors may create business-based opportunity structures that make particular types of insider financial frauds more or less likely to occur within a particular business. Originality/value: Existing research on insider financial frauds may not appropriately account for small businesses that cannot afford, or are unwilling, to hire a CFE. The findings discussed in this paper contribute to a more complete picture of the types of frauds that small businesses experience, as well as how these businesses deal with insider theft.